(untitled) (Kronika Bydgoska, 2013)
The author presents the 20-year history of the Competition for Young Pianists ”Arthur Rubinstein in memoriam” in the background of the region’s music culture and development of secondary and higher music education. She recalls the concert of Arthur Rubinstein at the Pomeranian Philharmonic in Bydgoszcz in 1960, and a stay of Karol Szymanowski in Bydgoszcz in the years 1921 and 1922, indicating these events as significant inspirations for the creation of the competition. She describes the nine successive editions of the competition, its program-artistic form, and laureates. She indicates the specificity of the competition for young pianists before 21 years of age, which gives them a special opportunity for promotion and development of their talent through recitals, as well as radio and TV recordings.